2002
DOI: 10.1007/s00276-002-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

A detailed anatomical description of the subvastus region and its clinical relevance for the subvastus approach in total knee arthroplasty

Abstract: The subvastus region and its anatomical contents are important when performing a total knee replacement via a subvastus approach. Thirty-two human cadaver thighs were studied to provide a detailed anatomical description of the subvastus region and its contents, namely the descending genicular artery and its branches, and the saphenous nerve proximally. In 24 specimens the descending genicular artery arose from the femoral artery and divided into osteoarticular and saphenous branches, while in eight specimens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 20 publications
2
18
0
2
Order By: Relevance
“…19 Scheibel et al indicated that the three branches of the descending genicular artery have one common origin, whereas the anatomical studies conducted by Hertel and Masquelet or Ballmer and Masquelet showed that, in most cases, all of the branches have independent origins. [44][45][46] These findings led us to conclude that the pedicles of the medial femur condyle flap have an abundance of anatomical variation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…19 Scheibel et al indicated that the three branches of the descending genicular artery have one common origin, whereas the anatomical studies conducted by Hertel and Masquelet or Ballmer and Masquelet showed that, in most cases, all of the branches have independent origins. [44][45][46] These findings led us to conclude that the pedicles of the medial femur condyle flap have an abundance of anatomical variation.…”
Section: Discussionmentioning
confidence: 93%
“…The limitation is, in part, attributable to the wide anatomical variation of the descending genicular artery, which has been observed in anatomical studies focusing on the medial descending genicular artery. 19,44,45 Dubois et al described five branch possibilities of the descending genicular artery. 19 Scheibel et al indicated that the three branches of the descending genicular artery have one common origin, whereas the anatomical studies conducted by Hertel and Masquelet or Ballmer and Masquelet showed that, in most cases, all of the branches have independent origins.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of this safe interval was also emphasized by Scheibel et al (20). In their study related with total knee replacement via a subvastus approach, they reported that the proximal limitation for the mobilization was the AH, in order not to damage the femoral artery and vein (20).…”
Section: Discussionmentioning
confidence: 99%
“…The DGA originates from the femoral artery at the level of the adductor hiatus Koshima et al 1988;Martin et al 1991;Scheibel et al 2002;Pan & Taylor, 2009;Dubois et al 2010;Yamamoto et al 2010;Rahmanian-Schwarz et al 2011;Gocmen-Mas et al 2012) and has been described to subdivide itself into three main branches a saphenous branch, a muscular branch and an osteoarticular branch (Hertel & Masquelet, 1989;Martin et al 1991;Ballmer & Masquelet, 1998;Scheibel et al 2002;Dubois et al 2010;Yamamoto et al 2010;Gocmen-Mas et al 2012;Garcia-Pumarino & Franco, 2014). The classification of three Table 3) does not only show a relative frequency of these patterns, but also explains why the muscular branch and the osteoarticular branch are often described as musculoarticular branch due to their frequent occurrence as common trunk Gocmen-Mas et al 2012).…”
Section: Dgamentioning
confidence: 99%